Prevalence and Clinical Associations of Antiphospholipid Antibodies in Systemic Sclerosis: New Data From a French Cross-Sectional Study, Systematic Review, and Meta-Analysis - Sobanski, Vincent; Lemaire-Olivier, Angélique; Giovannelli, Jonathan; Dauchet, Luc; Simon, Myriam; Lopez, Benjamin; Yelnik, Cécile; Lambert, Marc; Hatron, Pierre-Yves; Hachulla, Eric; Dubucquoi, Sylvain; Launay, David (Frontiers in Immunology, 2018)
Objectives. Antiphospholipid antibodies (aPL) can be present in the sera of systemic sclerosis (SSc) patients. This study aimed to determine the prevalence of aPL in a cross-sectional study of SSc patients, to assess their clinical associations, to perform a systematic review of published reports and a meta-analysis to estimate the worldwide prevalence of aPL in SSc. Methods. Two-hundred and forty-nine SSc patients were consecutively tested once for lupus anticoagulant (LA), anticardiolipin (aCL) and anti-β2glycoprotein I (anti-β2GpI) antibodies. Clinical associations with aPL positivity were studied using a logistic regression model. A systematic review of the literature was carried out in PubMed and Embase. Meta-analysis was performed using number of aPL positive (at least one of the three antibodies positive) and negative patients. Meta-regression was used to study potential factors explaining the heterogeneity between studies. Results. In our cross-sectional study, aPL positivity was found in 16 patients (prevalence 6.4%; 95%CI [3.8-10.4]). In multivariate analysis, there was a significant association between aPL positivity and venous thrombosis (VT) (OR 6.25 [1.18-33.00]; p=0.028) and miscarriage (OR 5.43; 95%CI [1.31-22.13]; p=0.017). Twenty-four studies were included in the meta-analysis, representing a total population of 3036 SSc patients. The overall pooled prevalence of aPL in SSc was 16% (10-22) with a high degree of heterogeneity among studies. Conclusion This study found a prevalence of aPL positivity in our SSc population of 6.4% (3.8-10.4) and an overall worldwide pooled prevalence of 14% (9-20). In our SSc population, aPL positivity was associated with VT and miscarriage. These data provide additional insights into the role of aPL in the vasculopathy observed in SSc.